Engineering and combining oncolytic measles virus for cancer therapy - Leber, Mathias Felix; Neault, Serge; Jirovec, Elise; Barkley, Russell; Said, Aida; Bell, John C.; Ungerechts, Guy (Cytokine & growth factor reviews, 2020)
Cancer immunotherapy using tumor-selective, oncolytic viruses is an emerging therapeutic option for solid and hematologic malignancies. A considerable variety of viruses ranging from small picornaviruses to large poxviruses are currently being investigated as potential candidates. In the early days of virotherapy, non-engineered wild-type or vaccine-strain viruses were employed. However, these viruses often did not fully satisfy the major criteria of safety and efficacy. Since the advent of reverse genetics systems for manipulating various classes of viruses, the field has shifted to developing genetically engineered viruses with an improved therapeutic index. In this review, we will summarize the concepts and strategies of multi-level genetic engineering of oncolytic measles virus, a prime candidate for cancer immunovirotherapy. Furthermore, we will provide a brief overview of measles virus-based multimodal combination therapies for improved tumor control and clinical efficacy.
Gesehen am 16.02.2021